Stunning method and time interval from stunning to bleeding effects on blood splashing in pork - Burson, D.E.; Hunt, Melvin C.; Schafer, D.E.; Beckwith, D.; Garrison, J.R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two studies were designed to test the effects of stunning method and time interval between stunning and bleeding on blood splashing in pork muscle. In study I, 82 market weight barrows and gilts were randomly assigned to one of two treatments using captive bolt stunning with either a short (18.5 sec) or a delayed (144.7 sec) time interval to bleeding. More (P<.05) blood splashing occurred in the ham, loin and shoulder of the delayed time group than in the short time group. In study II, 48 barrows and gilts were randomly assigned to one of four treatment combinations using either captive bolt or electric stunning with either a short (8.7 sec) or delayed (96.0 sec) time interval before bleeding. Carcasses in the captive bolt-delayed time group had more (P<.05) blood splashing in the diaphragm, fresh ham face and cured ham than in those muscles from the other treatment groups. Blood splashing in the diaphragm, ham face and cured ham were similar (P>.05) for the captive bolt-short, electric-short and electric-delayed time groups.
Keywords: Swine; Stunning; Blood splashing; Carcasses